Pemasaran Digital Berbasis CMS Wordpress Pada UMKM Shapro Official Wonogiri - Pipin Widyaningsih; Nurohman; Indah Nofikasari (STEKOM PRESS, 2022)
The COVID-19 pandemic had a significant impact on UMKM. Social distancing has changed consumer behavior from conventional to digital. UMKM Shapro Official is an original automotive t-shirt vendor that was established in 2017. Shapro Official has difficulty in introducing and marketing products with a clear target consumer and competitive price competition. Sales promotions have not been managed optimally and sales data management is still manual (notes). Owners also have difficulty monitoring sales reports in real time. Website created using CMS Wordpress to help Shapro Official difficulties. The system development method is Rapid Application Development (RAD). System analysis method using fishbone diagram and system modeling using Unified Modelling Language (UML). The results showed that the existence of a website can help the management to manage promotions, sales and sales reports. Having a website makes sales targets focus and increase.